Selection of efficiency evaluation models - BANKER, RAJIV D. (Contemporary Accounting Research, 1992)
The purpose of this paper is to emphasize the importance of selecting the efficiency evaluation model that best represents the known and postulated relation between inputs and outputs. By ignoring the input/output relationship, Mehrez, Brown, and Khouja (MBK) misspecify the efficiency evaluation model and misinterpret the distortions resulting from their misspecification as being paradoxical. This paper shows that the use of the appropriate data envelopment analysis (DEA) model reflecting the matched output/input (MOI) technology postulated by MBK will always provide efficiency estimates that satisfy their MOI axiom. Statistical consistency of the DEA estimator also implies that even with MBK's use of a misspecified model, the frequency of violation of their MOI axiom is likely to be small for large samples. Résumé. L'auteur insiste sur l'importance du choix du modèle de l'évaluation du rendement qui représente le mieux la relation connue et postulée entre les intrants et les extrants. En ignorant la relation intrant‐extrant, Mehrez, Brown et Khouja (MBK) définissent mal le modèle d'évaluation du rendement et jugent, à tort, les distorsions résultant de cette définition comme étant paradoxales. L'auteur démontre que le recours à l'analyse intégrale appropriée des données s'inspirant de la technologie de concordance extrant‐intrant postulée par MBK produit toujours des estimations du rendement qui respectent l'axiome de concordance. La cohérence statistique des estimations issues de l'analyse intégrale des données donne également à penser que même lorsqu'on utilise un modèle mal défini comme le font MBK, la fréquence des dérogations à l'axiome de concordance extrant‐intrant tend à être faible pour les gros échantillons.